Evaluasi dan Redesign Website Qema Farm Menggunakan Metode User Experience Lifecycle - Dwi Shahita; Reisa Permatasari; Nambi Sembilu (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to evaluate and redesign the Qema Farm website, a digital platform operating in the livestock sector and offering investment services through digital media. As user demands have increased, several usability issues have been identified, adversely affecting the overall user experience. An initial evaluation was conducted using the Heuristic Evaluation method, which revealed five usability problems, four categorized as cosmetic issues (severity rating 1) and one as a minor issue (severity rating 2). These findings indicate the need for improvements to enhance user interaction quality. Based on the evaluation results, a redesign process was carried out using the User Experience Lifecycle (UXL) method, encompassing the stages of analysis, design, prototyping, and evaluation. The redesigned interface was then tested through Usability Testing and the System Usability Scale (SUS) involving 6 respondents. Post-redesign evaluation demonstrated a significant improvement in the average usability score, increasing from 2.71 to 4.54 on a 5-point scale, with the highest score observed in the efficiency aspect (4.67). Additionally, the SUS score rose from an average of 57.50, classified as a “D” grade, to an average of 91.25, corresponding to an “A+” grade. These results demonstrate that the application of the UXL method was effective in enhancing both the interface quality and user experience of the Qema Farm website.